2011
DOI: 10.1590/s1677-55382011000300013
|View full text |Cite
|
Sign up to set email alerts
|

New ex-vivo organ model for percutaneous renal surgery

Abstract: Objectives: Percutaneous Renal Surgery (PRS) is a demanding procedure and success is mostly hampered by the lacking of training facilities. Thus, the purpose of the study was to evaluate a significantly improved pre-existing porcine kidneytraining model for percutaneous renal access and PRS. Materials and Methods: A biologic training model using porcine kidneys coated by a full-thickness porcine skin flap was prepared. The ureter was dissected, stones were placed into the collecting system using an 18F amplatz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Few studies were found on assessment of PCA skills. 12,13 The biological bench models used porcine or bovine kidneys wrapped within foam, 14 foam in a mannequin, 15 silicone, 16 chicken carcass, 17,18 full-thickness skin flap, 19,20 or additional subcutaneous fascia, muscle, 21 and ribs. 22 Other nonbiological bench models used prototyping or 3D printing.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies were found on assessment of PCA skills. 12,13 The biological bench models used porcine or bovine kidneys wrapped within foam, 14 foam in a mannequin, 15 silicone, 16 chicken carcass, 17,18 full-thickness skin flap, 19,20 or additional subcutaneous fascia, muscle, 21 and ribs. 22 Other nonbiological bench models used prototyping or 3D printing.…”
Section: Resultsmentioning
confidence: 99%
“…Hammond et al [9] and Häcker et al [10] used a porcine kidney in a chicken carcass. Zhang et al [11], Qiu et al [12] and Imkamp et al [13] used porcine kidney encased in skin or tissue flaps. Earp [14] used porcine kidney encased in a foam layer.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are few reports of structured training schemes [3] . A structured training programme, including acquiring technical and cognitive skills combined with clinical training under continuous mentoring and controlled conditions which ensure the safety of the patients, has not been proposed [2] , [3] , [5] , [6] , [10] , [11] , [12] , [13] . Structured training schemes such as the MTS have been described for laparoscopy [14] , [15] , [16] .…”
Section: Discussionmentioning
confidence: 99%